New appraisals of Kyrieleis plaques: a multimodal imaging study. Issue 3 (6th June 2016) - Pichi, Francesco; Veronese, Chiara; Lembo, Andrea; Invernizzi, Alessandro; Mantovani, Alessandro; Herbort, Carl P; Cunningham, Emmett T; Morara, Mariachiara; Ricci, Federico; Neri, Piergiorgio; Nucci, Paolo; Ciardella, Antonio P; et al.
Abstract : Purpose: Kyrieleis retinal periarteritis reflects the severe intraocular inflammation experienced by the eye. Its aetiology has not been well established, since only nine cases have been reported and there is no pathological study available in the literature. We determine the pathogenesis of Kyrieleis periarteritis based on interpretation of multimodal imaging findings. Methods: Charts of patients with Kyrieleis arteritis seen between 2006 and 2014 were retrieved from eight uveitis referral centres throughout the world. Follow-up ranged from 5 to 12 months. Results: Twenty-five eyes with Kyrieleis arteritis from 25 patients were included in the study. Nineteen patients (72%) were male and six (28%) were female. Twenty-three patients were diagnosed with toxoplasmosis retinochoroiditis and two patients had cytomegalovirus retinitis. Fluorescein angiography, fundus autofluorescence and indocyanine green angiography were performed on 25/25 (100%) eyes. In eight eyes (32%), baseline spectral domain optical coherence tomography (SD-OCT) scans were performed along the segmental Kyrieleis arteritis. Fluorescein angiography showed early hypofluorescence and intermediate hyperfluorescence associated with the areas of focal arteritis, whereas indocyanine green angiography of these accumulations showed early hypofluorescence and late hyperfluorescence. Fundus autofluorescence revealed an increased autofluorescence of the vessels corresponding to the Kyrieleis plaques, while SD-OCT scans along the segmental Kyrieleis arteritis showed hyperreflectivity of the vessel wall. Conclusions: These imaging modalities provide in vivo, quasi-histologic images demonstrating that Kyrieleis plaques are characterised by an inflammatory involvement within the vessels' endothelium.